High-Throughput Screening for Bacterial Glycosyltransferase Inhibitors - El Qaidi, Samir; Zhu, Congrui; McDonald, Peter; Roy, Anuradha; Maity, Pradip Kumar; Rane, Digamber; Perera, Chamani; Hardwidge, Philip R. (Frontiers in Cellular and Infection Microbiology, 2018)
The enteropathogenic and enterohemorrhagic Escherichia coli NleB proteins, as well as the Salmonella enterica SseK proteins are type III secretion system effectors that function as glycosyltransferase enzymes to post-translationally modify host substrates on arginine residues. This modification is unusual because it occurs on the guanidinium groups of arginines, which are poor nucleophiles, and is distinct from the activity of the mammalian O-linked N-acetylglucosaminyltransferase. We conducted high-throughput screening assays to identify small molecules that inhibit NleB/SseK activity. Two compounds, 100066N and 102644N, both significantly inhibited NleB1, SseK1, and SseK2 activities. Addition of these compounds to cultured mammalian cells was sufficient to inhibit NleB1 glycosylation of the tumor necrosis factor receptor type 1-associated DEATH domain protein. These compounds were also capable of inhibiting Salmonella enterica strain ATCC 14028 replication in mouse macrophage-like cells. Neither inhibitor was significantly toxic to mammalian cells, nor showed in vitro cross-reactivity with the mammalian O-linked N-acetylglucosaminyltransferase. These compounds or derivatives generated from medicinal chemistry refinements may have utility as a potential alternative therapeutic strategy to antibiotics or as reagents to further the study of bacterial glycosyltransferases.